Exploring the Therapeutic Potential of the DOT1L Inhibitor EPZ004777 Using Bioinformatics and Molecular Docking Approaches in Acute Myeloid Leukemia - Mehmet Kivrak; Ihsan Nalkiran; Hatice Sevim Nalkiran (Current Issues in Molecular Biology)
Background: Acute myeloid leukemia (AML) is a malignancy characterized by the clonal expansion of hematopoietic stem and progenitor cells, often associated with mutations such as NPM1. DOT1L inhibitors have shown potential as new therapeutic opportunities for NPM1-mutant AML. The aim of this study was to investigate potential alternative targets of the small-molecule inhibitor EPZ004777, in addition to its primary target, DOT1L, using RNA sequencing data from the NCBI-GEO database (GSE85107). Methods: Differentially expressed genes (DEGs) were identified through bioinformatic analysis, followed by pathway enrichment analysis to uncover the relevant biological pathways. Additionally, molecular docking analysis was conducted to assess the binding affinity of EPZ004777 with the proteins CT45A3, HOXA4, SNX19, TPBG, and ZNF185, which were identified as significantly DEGs. The protein structures were obtained from AlphaFold and the Protein Data Bank. Results: EPZ004777 significantly altered gene expression. Oncofetal genes (CT45A3, TPBG) and genes associated with oncogenic pathways (HOXA4, ZNF185, SNX19) were downregulated, while the pro-apoptotic gene BEX3 was upregulated. Pathway enrichment analysis revealed the suppression of the Rap1 signaling pathway and cell adhesion molecules, which may reduce the invasiveness of AML cells. Additionally, upregulation of immune-related pathways suggests enhanced anti-tumor immune responses. Molecular docking analysis demonstrated that EPZ004777 has strong binding potential with SNX19, TPBG, and ZNF185 proteins. Conclusions: EPZ004777 has been identified as a potent modulator of SNX19, TPBG, and ZNF185 associated with apoptosis and tumor progression in AML.